ANALYZING THE CONNECTION BETWEEN GYMNAST'S STATURE AND MEDAL PERFORMANCE ON APPARATUSES IN MEN'S ARTISTIC GYMNASTICS - Emre Bagci (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
In order to achieve success in sports, certain physical fitness characteristics are necessary. This study aims to determine whether a relationship exists between the height of male gymnasts who have won medals in the World Championships and Olympic Games in Artistic Gymnastics, and the apparatus on which they achieved those medals. Competitions in Men's Artistic Gymnastics at World Championships and Olympic Games are held in six apparatuses for individuals: floor exercise, pommel horse, rings, vault, parallel bars and horizontal bar. Each apparatus follows specific rules for evaluating gymnastics routines. Airborne acrobatics dominate on floor and vault, while support holds prominence on pommel horse and parallel bars, and hanging manoeuvres characterize rings and the high bar.  While a gymnast's body height influences all forms of gymnastics, the question remains: who can rise to the top on each apparatus? Within the scope of the research, the results between the years from 2009 to 2021 were examined. In this context, data from three Olympic Games (2012, 2016 and 2020) and nine World Championships (2009, 2010, 2011, 2013, 2014, 2015, 2017, 2018 and 2019) were used. The heights (251 sets of data) of the gymnasts who won medals in these competitions were evaluated. While the shortest of the medal-winning gymnasts was 150cm tall (floor exercise and pommel horse) and the tallest 183cm (floor exercise and horizontal bar), the average height of the medal-winning gymnasts was 164.67cm (± 6.12). There is statistically significant difference between the heights of the gymnasts who won medals on apparatuses (p<0.05).